(untitled) (TAJ: Journal of Teachers Association, 2021)
Background: Rajshahi medical college hospital is a tertiary care teaching and referral center in the North-West part of Bangladesh. To assess the epidemiological trend in hospital admission, including morbidity and mortality pattern of illness in the pediatric population, it needs to develop effective health care planning, appropriate resource allocation, and integration of existing health care service facilities. Objective: To evaluate the diseases and deaths of children admitted in the department of pediatrics, Rajshahi medical college hospital, Rajshahi. Materials and methods: This is a retrospective study. The collected case records of all patients admitted in the department of pediatrics from 1st January 2017 to 31st December 2019 (3 years) were analyzed. Result: A total of 62000 children were admitted during the mentioned study period. All the patients were distributed into three age groups infant, under five, and more than five, contributing 22%, 27.5%, and 19%, respectively. Acute watery diarrhea (21%), hereditary hemolytic anemia (18%), bronchopneumonia (10.4%), acute gastritis (9.4%), and acute bronchiolitis and wheezy child (7.17%) were the top five diseases in each of the three years of admission. Among the total admitted patients, 1003 (1.61%) patients died. Infant, under five, and more than five age groups constitute 61.3%, 28.1%, and 15.1%, respectively. Encephalitis and fulminant hepatic failure found the top two diseases causing death with a case fatality rate was 61% and 43%, respectively. The next highest case fatality rate was found in acute leukemia (15%). Other common causes of death include meningitis, cerebral palsy with complications (7.5%), bronchopneumonia with complications (3.8%). Conclusion: An admission-related comprehensive evaluation of this study will help to understand the diseases and death patterns of a hospital, leading to the development of more effective planning and case management strategies. TAJ 2021; 34: No-1: 55-62